PELAKSANAAN PERATURAN DAERAH NOMOR 2 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN (STUDI - Syafria Ningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research was conducted at the Departement of Trasportation in Pekanbaru is The Implementation Local Regulation Number 2 of 2009 About Trafficand Road Transport In The City of Pekanbaru (Case Study Have A Tonnage). The purpose of this study was to determine and analyze the Implementation Local Regulation Number 2 of 2009 About Trafficand Road Transport In The City of Pekanbaru (Case Study Have A Tonnage) And the factors that affect The Implementation Local Regulation Number 2 of 2009 About Trafficand Road Transport In The City of Pekanbaru (Case Study Have A Tonnage ).The concept of the theory of implementation by Merilee S. Grindle (Agustino:2012) : 1. Type of benefit, 2. Site of decision making, 3. Resources committed, 4. Institution and regime characteristic, 5. Compliance and responsiveness. This research uses qualitative research methods to the studi of descriptive data. In data collection, the author uses interview technique of triangulation as a source in the validaty of the data.The result of this research indicate that Implementation Local Regulation Number 2 Of 2009 About Trafficand Road Transport In The City of Pekanbaru (Case Study Have A Tonnage) yet feels maximum. Looked at violation prohibition of traffic sign by have a tonnage in Pekanbaru every years cause of society awareness. Not consistent in decision making, human resources make control of implementation be not maximum, not compliance and responsive by society.The factors that affect the Implementation Local Regulation Number 2 of 2009 About Trafficand Road Transport In The City of Pekanbaru (Case Study A Have Tonnage) is spread less socialization and sanction enforcement is not explicit.Keywords : Implementation. Trafficand Road Transport